Mauritius - Through the Eye of a Perfect Storm : Coming Back Stronger from the COVID Crisis - World Bank (World Bank, Washington, DC, 2021)
On July 1, 2020, Mauritius officially joined the ranks of High-Income Countries (HIC). It is a cruel historical irony that Mauritius reached the High-Income milestone during one of the worst years in its history. Mauritius delivered a highly successful health response to the global Covid-19 pandemic through a hard lockdown and subsequent quarantine measures, and as a result has effectively been ‘Covid-free’ from April 2020 to March 2021, when a second outbreak occurred. With a total of 1246 cases and 17 deaths, Mauritius has so far been able to avoid the large-scale health crisis observed in many other countries. However, Covid-19 has caused severe economic disruptions in Mauritius. An oil spill in August and Mauritius’ inclusion in the EU list of High Risk Third Countries for Money Laundering in October 2020 added further pressure. While the events of 2020 require dedicated responses in the short term, addressing the underlying challenges cannot be postponed if Mauritius is to make a strong recovery. The best strategy for a solid recovery lies in a combination of temporary support to firms and households affected by the shock with a comprehensive reform program to address pre-existing structural challenges. It is unlikely that a strategy of simply addressing the short-term effects by supporting ailing firms while waiting for global conditions to improve would suffice to put Mauritius’ economic and social development back on track. On the other hand, the crisis affords policy makers with the opportunity to confront long-festering challenges.